Business Communication and Entrepreneurial Motivation as Predictors of Micro-Enterprise Success Among Muslim Women in South Kalimantan - Sudarwati, Sudarwati; Ahmad, Ahmad; Umi Anisah , Hastin (Journal of Scientific Insights, 2025)
Muslim women entrepreneurs in peripheral regions face unique cultural, religious, and economic challenges that influence their microenterprise development. This study aims to examine the influence of entrepreneurial motivation and business communication on microenterprise success among Muslim women in South Kalimantan, Indonesia. Employing a quantitative, cross-sectional design, data were collected from 85 Muslim women micro-entrepreneurs through structured questionnaires. The instruments measured internal and external communication, intrinsic and extrinsic motivation, and multidimensional indicators of enterprise success. Statistical analysis using multiple linear regression (SPSS 26.0) revealed that both entrepreneurial motivation (β = 0.393, p < 0.001) and business communication (β = 0.431, p < 0.001) significantly and positively affect microenterprise success. The regression model explained 38.4% of the variance in business success (R² = 0.384). These findings highlight the critical role of soft skills—particularly motivation and communication—in sustaining business performance within culturally embedded environments. The study contributes to existing literature by integrating Self-Determination Theory and Relational Communication perspectives, and provides practical implications for designing gender- and culture-sensitive entrepreneurship support programs targeting Muslim women in marginalized areas.